Offer of authentic food as a condition for gastronomic tourism development - Kalenjuk, Bojana; Tešanović, Dragan; Gagić, Snježana; Erdeji, Irma; Banjac, Maja (The European Journal of Applied Economics, 2015)
By perceiving the food as an important part of the tourism offer in terms of biological needs of tourists, the question arises as to how it can be further exploited to contribute to tourism development. In this regard, food prepared using the local ingredients, according to the old methods of processing and serving, and in an authentic way, can be of interest to the tourists of selective forms of tourism, also known as food tourism, gastronomic tourism and gourmet tourism. The research aims to demonstrate the quality of food offer in the hospitality industry of Vojvodina and examine whether it can meet the requirements of foreign tourists who travel for it. The survey was conducted in 147 catering facilities in Vojvodina offering food and beverages, by means of direct and indirect collecting of written offers, and includes the statistical analysis of 10,923 meals. The aim is to indicate the current state of gastronomic offer and all advantages of authentic food and gastronomic tourism.